1997
DOI: 10.1359/jbmr.1997.12.9.1416
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase in Human Bone Tissue

Abstract: Peripheral aromatization of androgens exert estrogenic actions in many tissues. Recently in situ production of estrogens by aromatase was detected in human bone and cultured osteoblasts and has been proposed to participate in the maintenance of bone mass. We examined aromatase expression by immunohistochemistry and mRNA in situ hybridization in 16 cases of tibia (female 2 male, 14 female, 62 ؎ 5.2 years old) and quantified the level of aromatase mRNA in 28 cases of rib, femur, and lumbar vertebrae (16 male, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
137
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(143 citation statements)
references
References 38 publications
(64 reference statements)
4
137
0
2
Order By: Relevance
“…Several groups have shown that regulation of CYP19 gene expression is quite different in different tissues (12). The main promoters used are pII and I.3 in ovary, I.1 in placenta and I.4 in adipose stromal cells (10,22,23,46).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have shown that regulation of CYP19 gene expression is quite different in different tissues (12). The main promoters used are pII and I.3 in ovary, I.1 in placenta and I.4 in adipose stromal cells (10,22,23,46).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry and in situ hybridization have revealed that aromatase (CYP19) is expressed in osteoblasts, osteocytes, lining cells, and chondrocytes (5). Aromatase (CYP19) is the rate-limiting enzyme of estrogen biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In situ hybridization and immunohistochemistry have shown that aromatase immunoreactivity and gene transcripts are localized in lining cells, osteoblasts and chondrocytes of human bone tissue (Sasano et al 1997, Oz et al 2001. Some types of osteoclasts also express aromatase immunoreactivity (Oz et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…1). RT-PCR analysis indicates that the most dominant 5 UTR in aromatase gene transcript in human bone tissue is derived from upstream exon I.4 (Sasano et al 1997, Shozu & Simpson 1998). This suggests that the 5 region of exon I.4 (promoter I.4) is predominantly used in bone tissue to drive aromatase expression.…”
Section: Introductionmentioning
confidence: 99%